The Role of Instagram Influencers in Affecting Purchase Decision of Generation Z - Ghalib, Abie Syahrin; Ardiansyah, Muhril (Journal of Business, Management, and Social Studies, 2022)
Currently, social media is an online communication tool that made a huge impact on society. It makes social media a means for companies that want to attract the attention of potential consumers by utilizing the role of social media influencers who are considered to have great power and influence in the online world. An influencer could evaluate a product that consumers would admire, encouraging them to purchase it. A social media influencer has a significant role in consumer purchase intention. Hence, it is essential to analyze a factor that might affect a customer’s purchase intention. Therefore, this paper will examine the effect of Instagram influencers on customer purchase intention for Generation Z in Jakarta, Indonesia. An online questionnaire was used to collect the data from 162 respondents who are active Instagram users, currently living in Jakarta, following at least two Instagram influencers, and have purchased a product/service reviewed by Instagram influencers at least once. The findings indicate that Instagram influencers’ expertise and trustworthiness significantly affect customer purchase intention. Therefore, marketers and entrepreneurs in all sectors need to consider and engage with Instagram influencers as a strategy to increase customer purchase intention, particularly when planning to target Gen Z in Jakarta, Indonesia. Also, it can help them evaluate the long term impact that Instagram influencers may have on their business. This study will give a deeper understanding regarding the influence of influencer’s credibility, expertise, and trustworthiness toward Gen Z’s purchase intention.